The Impact of Brand Awareness and Country of Origin on Purchase Intention with Mediation of Self Congruity on Chinese Brand Automotive Products Wuling - Setiadi, Erick; Adiwijaya, Michael; Subagio, Hartono (Master of Management Study Program, Faculty of Business and Economics - Petra Christian University, 2018)
This study aims to analyze the relationship of Brand Awareness and Country of Origin by using Self Congruity as a mediation for Purchase Intention. This causal study used a questionnaire based survey as a data collection method and was distributed to 200 respondents which is a sample of this study. The selection of this research sample used a purposive sampling technique with criteria determined by the researcher. The results showed that the three hypotheses in this study have a significant influence and two hypotheses were rejected. all indicators on the related variables can be developed using PLS data (Partial Least Square). In addition, this study shows that Self Congruity as the most influential variables affecting respondents Purchase Intention toward Wuling car.